A Comprehensive Review of the Phytochemistry and Pharmacological Profiles of Musa acuminata (Family: Musaceae) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Musa acuminata, commonly called the banana plant, is a cornerstone of tropical agriculture and also in traditional medicine, recognized for its extensive phytochemical composition encompassing phenolic compounds, flavonoids, alkaloids, and terpenoids. Each segment of the plant includes the fruit pulp, peel, leaves, and pseudostem—harbors bioactive constituents that manifest a wide spectrum of pharmacological activities, such as anti-inflammatory, antimicrobial, antidiabetic, antioxidant, and cardiovascular effects. This review consolidates traditional knowledge and contemporary research to elucidate the therapeutic potential of M. acuminata in modern medicine. It underscores the imperative for further investigation into the plant’s genetic attributes to fully harness its pharmacological capabilities. By highlighting both the nutritional value and the diverse traditional and prospective therapeutic applications, this review provides a foundational framework for future research endeavors aimed at advancing global health and agriculture through the utilization of M. acuminata.